Walking Program of Low or Vigorous Intensity During Pregnancy Confers an Aerobic Benefit - Ruchat, S.-M.; Davenport, M. H.; Giroux, I.; Hillier, M.; Batada, A.; Sopper, M. M.; Hammond, J.-A.; Mottola, M. (International Journal of Sports Medicine, 2012)
Walking is the most popular activity during pregnancy and may confer an aerobic benefit. However, the minimum intensity threshold of a maternal walking program for an aerobic conditioning response is unknown. The purpose was to examine the effect of a walking program of a low-intensity (LI, 30% heart rate reserve, HRR) or vigorous-intensity (VI, 70%HRR) on maternal cardiorespiratory responses to a standard submaximal treadmill test. Normal weight pregnant women were randomized at study entry (16–20 weeks of gestation) to the LI (n=23) or VI (n=21) walking program, with nutritional control. Participants performed a steady-state treadmill exercise test at their prescribed intensity pre- and post-intervention (34–36 weeks) to evaluate changes in cardiorespiratory responses. Increasing body mass due to pregnancy was similar between the groups throughout the study. From pre- to post-intervention, relative (mL kg − 1 min − 1) VO2 and VCO2 during steady-state submaximal treadmill exercise did not change in the LI group but decreased in the VI group (− 1.25±2.71, p=0.02 and  − 1.50±2.64, p=0.005, respectively). Both groups presented increases in oxygen pulse (p≤0.002). Our results showed that the energy cost of walking was not affected by the increase in maternal body weight in the LI group and was decreased in the VI group, suggesting an aerobic conditioning response in both groups, although the VI group presented a greater response. All women presented similar body mass throughout the intervention and delivered healthy babies, indicating that a prenatal walking program of low or vigorous intensity, combined with healthy eating habits, is safe and beneficial to the mother and fetus.
Keywords: pregnancy; walking program; exercise intensity; nutritional control; cardiorespiratory responses